Reprogramming resistant genes: in-depth comparison of gene expressions among iPS, ES, and somatic cells - Polouliakh, Natalia (Frontiers in Physiology, 2013)
Transcription factor based reprogramming reverts adult cells to an embryonic state, yielding potential for generating different tissue types. However, recent reports indicated the substantial differences in pattern of gene expression between induced pluripotent stem (iPS) cells and embryonic stem (ES) cells. In this study we compare gene expression signatures of different iPS and ES cell lines and relate expression profiles of differently expressed genes to their expression status in somatic cells. As a result, we discovered that genes resistant to reprogramming comprise two major clusters, which are reprogramming dependent ‘Induced Genes’ and somatic origin ‘Inherited Genes’, both exhibiting preferences in methylation marks. Closer look into the Induced Genes by means of the transcription regulation analysis predicted several groups of genes with various roles in reprogramming and transgene DNA binding model. We believe that our results are a helpful source for biologists for further improvement of iPS cell technology.